ChemInform Abstract: Privileged Structures: Efficient Chemical "Navigators" Toward Unexplored Biologically Relevant Chemical Spaces. Issue 9 (March 2015) - Kim, Jonghoon; Kim, Heejun; Park, Seung Bum
Abstract Review: 104 refs.